REDESAIN USER INTERFACE DAN USER EXPERIENCE WEBSITE PENJUALAN BATIK MENGGUNAKAN METODE DESIGN THINKING: REDESIGN USER INTERFACE AND USER EXPERIENCE OF BATIK SALES WEBSITE USING DESIGN THINKING METHOD - Mutiara Kurnia Sari; Acihmah Sidauruk; Moch Farid Fauzi; Dhimas Adi Satria; Istiningsih Istiningsih (LPPM Universitas Abdurrab, 2024)
activities. This convenience can be realized by having a sales website that can display various types of products offered and can carry out transactions on the available websites. BatikUnik is one example that provides a platform for selling various types of batik products, so that customer comfort and convenience when accessing the website is of great concern, because the appearance of the website is still considered less attractive and less efficient. So a good experience and ease of browsing the website is the goal of updating the appearance of the website. Based on the problem found, this research will re-design the user interface and user experience of the batik clothing sales website using the design thinking method which produces a website design prototype that will be updated. The System Usability Scale was used to carry out a usability test using an old website which resulted in a 35.5 adjective rating of